Baseline Survey Dataset on Agricultural Practices, Dietary Diversity, and Socio-Economic Indicators in Vihiga County, Kenya (2018) - Termote, Celine; Aluso, Lillian Olimba; Akingbemisilu, Tosin Harold (2025)
This dataset originates from a baseline survey conducted between November 12 and November 30, 2018, in Vihiga County, Kenya. The survey was part of the project titled "Improving access to and benefits from a wealth of diverse seeds to support on-farm biodiversity for healthy people in resilient landscapes." The primary purpose of the study was to assess key indicators of agricultural practices, dietary diversity, socio-economic status, and food security at the household level. It aimed to establish a foundational understanding of the community's agricultural and nutritional landscape, serving as a benchmark for future interventions. The dataset includes detailed information on demographic and socio-economic characteristics, household income, market access, wealth profiles, household food security, dietary changes, maternal nutritional knowledge, and attitudes. Additionally, it captures household agricultural practices, including the adoption of climate-smart technologies, social seed networks for traditional leafy vegetables and legumes, and smart poultry farming practices. Quantitative 24-hour dietary recall data for women and children was also collected to assess dietary diversity and nutritional adequacy. The principal investigators sought to answer key questions such as: i) What is the current state of dietary diversity and nutritional practices among women and children? ii) How are socio-economic factors and market access influencing household food security? iii) What role do agricultural practices and farm diversity play in household resilience and nutrition? iv) What are the existing knowledge, attitudes, and practices surrounding maternal nutrition and climate-smart farming technologies? This dataset provides a comprehensive snapshot of the intervention and comparison sites, enabling insights into the baseline conditions and laying the groundwork for evaluating the project's impact.